A novel fry1 allele reveals the existence of a mutant phenotype unrelated to 5′->3′ exoribonuclease (XRN) activities in Arabidopsis thaliana roots - Hirsch, Judith; Maizel, Alexis (PLOS ONE, 2011)
Background Mutations in the FRY1/SAL1 Arabidopsis locus are highly pleiotropic, affecting drought tolerance, leaf shape and root growth. FRY1 encodes a nucleotide phosphatase that in vitro has inositol polyphosphate 1-phosphatase and 3′,(2′),5′-bisphosphate nucleotide phosphatase activities. It is not clear which activity mediates each of the diverse biological functions of FRY1 in planta. Principal Findings A fry1 mutant was identified in a genetic screen for Arabidopsis mutants deregulated in the expression of Pi High affinity Transporter 1;4 (PHT1;4). Histological analysis revealed that, in roots, FRY1 expression was restricted to the stele and meristems. The fry1 mutant displayed an altered root architecture phenotype and an increased drought tolerance. All of the phenotypes analyzed were complemented with the AHL gene encoding a protein that converts 3′-polyadenosine 5′-phosphate (PAP) into AMP and Pi. PAP is known to inhibit exoribonucleases (XRN) in vitro. Accordingly, an xrn triple mutant with mutations in all three XRNs shared the fry1 drought tolerance and root architecture phenotypes. Interestingly these two traits were also complemented by grafting, revealing that drought tolerance was primarily conferred by the rosette and that the root architecture can be complemented by long-distance regulation derived from leaves. By contrast, PHT1 expression was not altered in xrn mutants or in grafting experiments. Thus, PHT1 up-regulation probably resulted from a local depletion of Pi in the fry1 stele. This hypothesis is supported by the identification of other genes modulated by Pi deficiency in the stele, which are found induced in a fry1 background. Conclusions/Significance Our results indicate that the 3′,(2′),5′-bisphosphate nucleotide phosphatase activity of FRY1 is involved in long-distance as well as local regulatory activities in roots. The local up-regulation of PHT1 genes transcription in roots likely results from local depletion of Pi and is independent of the XRNs.